2005
DOI: 10.1080/00087114.2005.10589426
|View full text |Cite
|
Sign up to set email alerts
|

The effect of putrescine and difluoromethylornithine on cell division activity of wheat in different ploidy level

Abstract: -Effects of exogenous putrescine (Put) and difluoromethylornithine (DFMO) on seed germination, root growth, mitotic activity and mitotic chromosome behavior were investigated in Triticum monococcum (2x), Triticum durum (4x) and Triticum aestivum (6x). Put and DFMO affected all three species, but diploid species was the most affected one in respect to seed germination, mitotic index and the occurrence of abnormality than the others. Reduction of the root growth in Put and DFMO treated samples was due to the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…polyamines under Zea mays, also showed inhibitory effects on various cellular activities. Putrescine phytotoxicity is also described by Meral et al (2005), where the authors report the inhibition of root growth in Arabidopsis thaliana exposed to high concentrations of these BAs, which corroborates this present study. In addition, the authors also report that PUT had the capacity to decrease the GI of three wheat species with different ploidy levels.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…polyamines under Zea mays, also showed inhibitory effects on various cellular activities. Putrescine phytotoxicity is also described by Meral et al (2005), where the authors report the inhibition of root growth in Arabidopsis thaliana exposed to high concentrations of these BAs, which corroborates this present study. In addition, the authors also report that PUT had the capacity to decrease the GI of three wheat species with different ploidy levels.…”
Section: Resultssupporting
confidence: 92%
“…Wójcik et al (2020), point to the reactivity of these amines with other compounds, such as nitrite, forming carcinogenic compounds, such as nitrosamines. Unal et al (2008) also showed cytogenotoxic potential in meristematic cells of A. cepa exposed to different concentrations of PUT, and Meral et al (2005), reported the toxic effect of these BAs on seed germination, root elongation and chromosomal alterations in wheat.…”
Section: Introductionmentioning
confidence: 95%
“…This brings to the sub chromatid association; apart from the above stickness might be the result of action of herbicides on the protein of the chromosome [23]. Chromosomal bridges have been reported following treatment with number of chemicals including 2,4-D and isoproturon on wheat [21], Fieldr and Ronstar on wheat [16], imazethapyr on wheat [19], ethylene glycol on wheat [28], putrescine on wheat [24], maleic hydrazide on Trigonella [25], illoxan on Allium cepa [15]. Presence of chromosomal bridge may be due to stickness or formation of dicentric chromosome caused by breakage and reunion [25].…”
Section: Resultsmentioning
confidence: 99%